The Influence Of River Discharges, Tides, And Winds On Estuarine Plume In Northwest Peninsular Malaysia - Syukri, Muhammad (2006)
The aim of the thesis was to investigate the spatial and temporal structure of estuarine plume and coastal waters in northwest Peninsular Malaysia. Measurements of salinity, temperature, and TSS were carried out at the Muda plume, Prai plume and the lower Merbok estuary. In addition, aerial images and current measurements were also obtained through several selected field surveys. The discharge of the Muda River was an order of magnitude more than Prai and Merbok Rivers. The results suggest that the surface plume characteristics of the estuaries and coastal waters are influenced by freshwater discharge. spring-neap tidal energy, and to some extent by wind forcing. During high discharge, the offshore extent of the Muda and Prai estuary plumes were approximately 4 km and 2 km respectively. The surface horizontal areas covered by these plumes were 30.0 km2 and 13.5 km2, respectively. During low discharge, the extent of plumes were closer to the coastline at about 1-2 km offshore. Tides were responsible for the mixing and the stratification of the plumes. The Muda plume and the lower Merbok Estuary. during the transition of spring-to-neap periods that change the plume structure from partially-mixed or homogeneous (spring tide) to highly stratified (neap tide). There were consistently higher TSS concentrations of Muda and Prai plume waters and Merbok Estuary during spring tides than at neap tides due to stronger spring tide energy. On the contrary, during neap tide a similar behavior of TSS concentration was not found. No obvious correlation was found between the plume characteristics and wind forcing, except during strong winds when there were some evidence of plume movement according to wind direction. Remote sensing provided information on the two-dimensional surface structures of the estuary plumes. For example, the aerial images clearly showed snapshots of the Prai plume being deflected to the south/north during low/high discharge. These behaviors were influenced by tides.